Day 3 Tue, April 25, 2017 2017
DOI: 10.2118/185649-ms
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpretation of Fracture Closure Dynamics During Diagnostic Fracture Injection Tests

Abstract: A fit-for-purpose, fully coupled stress-pore pressure simulation model (Abaqus®) is used to simulate diagnostic fracture injection tests (DFITs) and generate before closure pressure responses. The simulated responses are used to explain field observations, and to propose a new concept: progressive fracture closure. The cohesive zone model (CZM) is used to model fracture propagation and closure associated with DFITs. The customized model in Abaqus® is capable of modeling all the physical processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…DFIT is a standard tool for reservoir analysis [53][54][55][56], but conventional approaches often fall short in accurately determining reservoir attributes. A novel type-curves approach has been developed to increase the reliability of DFIT outcomes, thereby improving the Vaca Muerta reservoir characterization.…”
Section: Diagnostic Fracture Injection Test (Dfit) New Approachmentioning
confidence: 99%
“…DFIT is a standard tool for reservoir analysis [53][54][55][56], but conventional approaches often fall short in accurately determining reservoir attributes. A novel type-curves approach has been developed to increase the reliability of DFIT outcomes, thereby improving the Vaca Muerta reservoir characterization.…”
Section: Diagnostic Fracture Injection Test (Dfit) New Approachmentioning
confidence: 99%
“…Another fracture model was then introduced by [126] to investigate the behavior of the fracture closure. They confirmed the observation of McClure et al [124] which states that the fracture closure pressure may be underestimated when the DFIT data are interpreted using the tangent line method, and they recommended the compliance method as a more reliable approach.…”
Section: Common Data Acquisitionmentioning
confidence: 99%
“…McClure et al (2016) modeled fracture closure behavior using a fully coupled numerical simulator and found that the "tangent line method" can severely underestimate closure pressure, and based on the simulation results, they proposed a "compliance method" for picking closure pressure on the G-function plot, where closure pressure is picked at the point where the fracture stiffness starts to increase. Zanganeh et al (2017) presented a cohesive zone fracture model to investigate fracture closure behavior, and their results also show that using the "tangent line method" or using the end of 3/2 slope on a log-log plot can underestimate closure pressure, and that the "compliance method" is a more reliable approach. However, fracture stiffness (or compliance) can change continuously during the fracture closure process, because the fracture does not close all at once, but rather closes on asperities progressively from its edges to the center .…”
Section: Fig 1 Diagram Showing Sequence Of Events Observed In a Dfitmentioning
confidence: 99%